Predicting stock returns with economic value added in the Stock Exchange of Singapore - Chia, Huey Ping. (2008)
The report investigates the usefulness of EVA as a stock return predictor. It also compares EVA with other financial ratios like price-earnings, market-to-book and return on equity in predicting superior stock returns.